THE INFLUENCE OF OIL CAKE GRANULATION AND ULTRASONIC PRETREATMENT ON THE PROPERTIES OF BIOPOLYMER FILMS BASED ON CAMELINA SATIVA OILSEED CAKE - Šuput, Danijela; Popović, Senka; Hromiš, Nevena; Rakita, Slađana; Spasevski, Nedeljka; Lončar, Biljana; Erceg, Tamara; Knežević, Violeta (Food and Feed Research, 2023)
This study aimed at investigating the synthesis of biopolymer films based on the Camelina sativa cake, an agricultural waste which remains after cold pressing of the oil from seed. During the film synthesis, three different granulations of the camelina cake were used: the whole cake, fractions with a size of 180-250 µm and fractions smaller than 180 µm. Half of the samples were pretreated with an ultrasonic bath in order to examine the influence of the native mucilage from the cake on the properties of the obtained films. The biopolymer film samples were tested for mechanical, barrier, physicochemical and structural properties. The obtained films were dark, firm and flexible. Application of mucilage removal pretreatment contributed to lower tensile strength and higher elongation at break. Significantly lower water vapour permeability was recorded in the samples not pre-treated regarding mucilage removal. A foil with optimal physicochemical characteristics was produced using oilcake with a particle size less than 180 µm, regardless of the pre-treatment application. There were no structural differences or differences in thermal behaviour among the tested samples. Statistical analysis (Z-Score analysis) showed the sample CSoC˂180,wo was optimal due to good mechanical, barrier and physicochemical properties.